Computer and internet management - Goel, S K (New Delhi Rajat, 1999)
Computer and Internet Management book is in two Volumes. Internet network management functions can be part of the network operation centre. The process of management is a continuing one. Quality information could support good decision Many executive appar
Keywords: Internet (Computer network); Computer networks; Telecommunication; Database management